2008
DOI: 10.1007/978-1-59745-321-9_30
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Gene Essentiality Using Genome-Scale in Silico Models

Abstract: Genome-scale metabolic models of organisms can be reconstructed using annotated genome sequence information, well-curated databases, and primary research literature. The metabolic reaction stoichiometry and other physicochemical factors are incorporated into the model, thus imposing constraints that represent restrictions on phenotypic behavior. Based on this premise, the theoretical capabilities of the metabolic network can be assessed by using a mathematical technique known as flux balance analysis (FBA). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 92 publications
0
52
0
Order By: Relevance
“…As there is no measured or predicted biomass composition published for F. tularensis , for this organism we used the biomass components of Gram-negative E. coli MG1655 strain [15], [16]. Similarly, for B. anthracis , we used a close relative Gram-positive Bacillus subtilis strain 168 [33] and for Y. pestis , we again used E. coli MG1655 biomass components [15], [16], [17], [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is no measured or predicted biomass composition published for F. tularensis , for this organism we used the biomass components of Gram-negative E. coli MG1655 strain [15], [16]. Similarly, for B. anthracis , we used a close relative Gram-positive Bacillus subtilis strain 168 [33] and for Y. pestis , we again used E. coli MG1655 biomass components [15], [16], [17], [18].…”
Section: Methodsmentioning
confidence: 99%
“…Identifying gene essentiality by experimental approaches either using transposon mutagenesis or RNA silencing is time consuming and expensive, and the results are strain-specific. In contrast, computational methods provide an alternate approach for the identification of single essential and synthetic lethal metabolic enzymes [10], [15], [16], [17], [18] that can be simultaneously tested for multiple strains [16], [19]. These methods can be also tested simultaneously under several growth conditions and identify organism/strain specific essential metabolic enzymes as common drug targets.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggested that highly connected nodes or “hubs” are more likely to be essential (Hahn and Kern, 2005; Joyce and Palsson, 2008). For instance, in 2005, Hann and Kern compared centrality and essentiality in yeast, worm and fly PPI networks and concluded that a protein connectivity has an effect on the probability of being essential (Hahn and Kern, 2005).…”
Section: First Strategy: Use Of Individual Classical Centrality Indexmentioning
confidence: 99%
“…Targets for possible genetic manipulation to improve strain performance can be identified through comparative studies under both genetic and environmental perturbations. The model can then be used to calculate knockout lethality or growth rates, and results can be compared to experimental observations, which allows for the model to be iteratively tested and improved [40]. Several computational approaches for network manipulation and phenotypic simulation have been developed, such as the COBRA Toolbox for MATLAB [10], a popular FBA simulator.…”
Section: Automated Reconstructionsmentioning
confidence: 99%